2018
DOI: 10.1038/s41598-018-23376-5
|View full text |Cite
|
Sign up to set email alerts
|

Operating length and velocity of human vastus lateralis muscle during walking and running

Abstract: According to the force-length-velocity relationships, the muscle force potential during locomotion is determined by the operating fibre length and velocity. We measured fascicle and muscle-tendon unit length and velocity as well as the activity of the human vastus lateralis muscle (VL) during walking and running. Furthermore, we determined the VL force-length relationship experimentally and calculated the force-length and force-velocity potentials (i.e. fraction of maximum force according to the force-length-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 56 publications
4
120
0
1
Order By: Relevance
“…Recently, the functional indexing methods used here were combined with computational simulations of human walking to derive muscle-and MTU-specific mechanical functions and found that the biarticular rectus femoris acts more like a damper while the uniarticular vastus lateralis acts more like a spring (Lai et al, 2019). In line with this, evidence recently emerged highlighting the importance of series elastic elementsand thus, the spring-like capacityof the vastus lateralis during human locomotion (Bohm et al, 2018). Those authors were surprised to find that muscle fibers in the vastus lateralis acted near isometrically while walking at 1.5 m s −1 , suggesting that much of the mechanical work at the joint was being performed via spring-like behavior.…”
Section: Anklesupporting
confidence: 55%
“…Recently, the functional indexing methods used here were combined with computational simulations of human walking to derive muscle-and MTU-specific mechanical functions and found that the biarticular rectus femoris acts more like a damper while the uniarticular vastus lateralis acts more like a spring (Lai et al, 2019). In line with this, evidence recently emerged highlighting the importance of series elastic elementsand thus, the spring-like capacityof the vastus lateralis during human locomotion (Bohm et al, 2018). Those authors were surprised to find that muscle fibers in the vastus lateralis acted near isometrically while walking at 1.5 m s −1 , suggesting that much of the mechanical work at the joint was being performed via spring-like behavior.…”
Section: Anklesupporting
confidence: 55%
“…Rather, that the tendinous element facilitates lengthening and the fascicles remain closer to isometric. However, it should be noted that this proposal is based on evidence from other lower limb muscles 57,58 and animal studies, 59 and at this time, there is no direct evidence for this theory in the human hamstring muscles during running. Quasi-isometric fascicle behavior has been previously observed during highspeed running at the ankle plantar-flexor complex and also in the vastus lateralis.…”
Section: Musculotendon Length Changesmentioning
confidence: 90%
“…Quasi-isometric fascicle behavior has been previously observed during highspeed running at the ankle plantar-flexor complex and also in the vastus lateralis. 57,58 While we cannot assume that this fascicle behavior applies also to the hamstrings during running, it may suggest that these phenomena are plausible. Further, both Chumanov et al 50 and Thelen et al 49 have differentiated BFlh muscle and tendon contributions to lengthening using musculo-skeletal modeling, and predicted small discrepancies in lengthening patterns between the two elements.…”
Section: Musculotendon Length Changesmentioning
confidence: 92%
See 1 more Smart Citation
“…This might be an indication of the double function of this muscle: knee extensor and hip flexor. In fact, in the weight acceptance phase of the gait cycle, the quadriceps muscle group is known to aid the deceleration and support of the body mass, acting in a quasi-isometric way at the muscle fascicle level [63]. In the early swing phase, the 305 iliopsoas (iliacus and psoas) muscle group is one of the major contributors to the hip flexion, which starts right after the lift-off and continues for around three quarters of the swing phase [64][65][66][67][68].…”
Section: Fast Locomotion Requires Different Muscle Contributionsmentioning
confidence: 99%